Iconic-Conventional Myth Synergy - Oleksandr Soletskyi (Journal of Vasyl Stefanyk Precarpathian National University)
The article dwells on the problem of the iconic-conventional synergy of a myth. The myth is seen as a concept with a multifunctional status, blurred by identification attempts. Conceptual usage emphasizes its overlapping features that sport multifaceted practical typicality. As a system a myth embodies a worldview, a metaphysical form of a specifically structured narrative. Mythological consciousness includes specifically formed links between objects and phenomena, actions and cycles, all forming a system of iconic-conventional correlations. In this co-action the semantic core of a myth as a discourse is concentrated, its "symbolic matrix" is revealed, and the cognitive orientation and axiology are stated.